Spontaneous spinal subarachnoid haemorrhage: a rare complication of dengue fever / Nur Hidayati Mohd Sharif … [et al.] - Mohd Sharif, Nur Hidayati; Misnan, Nor Arisah; Saidon, Norashikin; Hashim, Hilwati (Universiti Teknologi MARA Cawangan Selangor, 2017)
A 37-year-old woman presented with a short history of fever and bilateral lower limb weakness. She also had impaired sensory function up to T4 spine level and lax anal tone. Laboratory investigations confirmed dengue infection with mild thrombocytopenia. MRI of the spine showed a spinal subarachnoid haemorrhage from the level of T4 till T9. Despite medical and surgical interventions, her lower limb weakness persists. A high index of suspicion is needed to recognise dengue-related neurological complications. This diagnosis should be considered in any patients from dengue endemic areas presenting with acute febrile illness with atypical neurological manifestations.